An Overview of the Development of Management Accounting Research (Malaysian Management Journal, 2003)
There has been significant changes in the direction of management accounting research since the 1980’s and 1990’s, from the prescriptive and normative research of the late 1950’s and 1960’s to the positivistic research in the 1970’s and 1980’s. As such, the purpose of this article is to provide an overview of this development. First, the paper discusses the characteristics of traditional management accounting research. Then, a reflection is given on the debate, which started in the 1980’s regarding the limitations of traditional management accounting research. It could be said that the 1980’s was a decade of re-evaluation for management accounting, both in terms of the research undertaken and in terms of techniques and practices. Now, various theoretical frameworks are used by researchers and new and innovative techniques are being implemented in organisations. The scope of management accounting has also been broadened from those based on economics perspective to a broader based approach.